Effects of galactooligosaccharides on maternal metabolism and the gut microbiota during pregnancy - Wan, Jiayang; An, Lin; Ren, Zhenghong; Yang, Huixia; Ma, Jingmei (Frontiers in Microbiology, 2026)
BackgroundThe gut microbiota of pregnant women changes dynamically throughout gestation, adapting to the physiological changes of pregnancy. At the same time, dysbacteriosis is involved in the pathophysiological processes of pregnancy-related diseases. Research on gut microbiota and gestational diabetes mellitus (GDM) is relatively extensive, and targeting the gut microbiota may improve maternal health. Dietary supplements such as prebiotics improve metabolic immune function in pregnant women by stimulating the growth of beneficial bacteria and promoting the production of short-chain fatty acids (SCFAs). Previous animal studies suggest that prebiotic preparations derived from galactooligosaccharides (GOS) in human milk are superior to other prebiotics.ObjectiveThis study aims to explore the systemic effects of GOS targeting the gut microbiota on the levels of metabolism, immunity, and circulating SCFAs.Materials and methods(1) A total of 135 pregnant women with available delivery outcomes and matched BMI were included in the analysis. From the first trimester (T1), the GOS group and the control group received GOS and fructooligosaccharide (FOS) preparations, respectively. Before the intervention (T1) and after the intervention (T2), blood samples were collected from pregnant women for LC–MS metabolomic analysis and targeted detection of short-chain fatty acids. At the same time, clinical information, metabolic indicators, and the GDM incidence rate were compared between groups, and subgroup analyses were conducted for overweight and obese participants. Statistical analyses included the t-test, the nonparametric Wilcoxon test, and the χ2 test. Correlation analysis was conducted using Fisher’s exact test and Pearson’s coefficient. (2) In order to examine the correlation between targeted gut microbiota intervention and phenotypic changes, 52 pregnant women who provided stool samples before and after the intervention (i.e., T1 and T2) were analyzed. The 16S rRNA V3–V4 variable region was sequenced on the Illumina HiSeq 2,500 platform, and QIIME was used for bioinformatics analysis. The correlations among differential flora, glycolipid metabolism, inflammatory factors, and metabolites were analyzed.Results(1) Non-target metabolites identified several metabolites with inter-group differences: cyclamate, reserpic acid, and phenylbenzimidazole sulfonic acid were relatively higher in the GOS group. Pathway analysis indicated enrichment in butyrate, propionate, and other SCFA-related metabolic pathways, as well as in cysteine and methionine metabolism. (2) The targeted metabolites of SCFAs were further analyzed, and the effects of the intervention on SCFAs were compared. After GOS intervention, the levels of acetic acid, propionic acid, butyric acid, and hexanoic acid all increased (p < 0.01). Among overweight and obese pregnant women with GDM, GOS increased the levels of butyric acid and hexanoic acid (p < 0.05). At T2, compared with the control group, hexanoic acid levels in the GOS group increased significantly (p < 0.01). Correlation analysis with clinical glucose and lipid metabolism indices showed that hexanoic acid was negatively correlated with total cholesterol (TCHO) (r = −0.415, p < 0.001) and LDL (r = −0.347, p < 0.01). (3) The relative abundance of different flora was correlated with glycolipid metabolism indices and inflammatory factors. The relative abundance of Dorea showed a negative correlation trend with TCHO and LDL. Additionally, the relative abundance of different flora was also correlated with circulating SCFAs. The relative abundance of Dorea and Paraprevotella showed a positive correlation trend with hexanoic acid.ConclusionGOS preparations containing ingredients derived from human milk may target the gut microbiota to promote the production of hexanoic acid, thereby improving lipid metabolism and inflammation, and may be beneficial for overweight and obese people with GDM.